Designing a Livestock Ecosystem Platform for Smallholders Farmers - Faza, Iqbal; Jasmine, Tamara Latifah (Institut Ilmu Sosial dan Manajemen Stiami, 2022)
This research aims to develop and create a simple of user-friendly marketplace platform called “Pasar Kebo for the farming (livestock) ecosystem in Kudus Regency as well as testing the effectiveness of the product. With this platform, it is hoped to create an integrated farming ecosystem, thereby creating an efficient supply chain management system. This will make it easier for smallholder farmers to obtain livestock production facilities to sell their livestock products in the market. So this will certainly improve the welfare of the livestock ecosystem members. For the government, this platform can be useful to provide accurate data in the mapping and monitoring of animal production, as well as a basis for the implementation of appropriate policies in the livestock sector. Data collection was accomplished through direct interviews with several Kudus breeders as well as observations at the Office of Agriculture in the Kudus Regency livestock sector.This research is longitudinal, so it will be carried out in stages, and each stage uses a different method. For this step, we tried to develop a prototype. For the next stage, it will be developed until this breeding ecosystem market platform is really perfectly realized.